Racing to the top: descent ideologies and why Ladinos never meant to be mestizos in colonial Guatemala. Issue 3 (1st September 2016) - Watanabe, John M.
ABSTRACT: This paper asks what mestizaje as presently conceived could have meant in colonial Latin America before modern notions of race, nation, state, or culture. It explores the term ladino in contemporary Chiapas and Guatemala that refers to people of mixed descent who identify as 'not Indian.' More than a substitute for mestizo, ladino represents a descent ideology that stresses parentage over race in pursuit of relative advantage within a stratified, postconquest society. This descent ideology in turn derives from the 'republics' of Spaniards and Indians – and African slaves – in colonial Guatemala, and post-Reconquest Iberian ideals of 'purity of blood' based on, not race, but legitimate birth to a Christian family going back to before the Muslim conquest of Spain. The vagaries of genealogical reckoning inherent in descent ideologies help to rationalize why from the bottom up 'mestizo' identities came to depend as much on behavior as appearance, and from the top down, they provoked blanket phenotypic exclusions that eventually, but not primordially, found validation in biologized conceptions of race.